Applications of Human Skin Microbiota in the Cutaneous Disorders for Ecology-Based Therapy - Zhou, Hong; Shi, Linlin; Ren, Yuanyuan; Tan, Xi; Liu, Wei; Liu, Zhi (Frontiers in Cellular and Infection Microbiology, 2020)
The skin represents the exterior interface between the human body with the environment while providing a home to trillions of the commensal microorganisms—collectively referred to as the skin microbiota. These microbes that coexist in an established balance play a pivotal role in the protection of cutaneous health and the orchestration of skin homeostasis. However, the well-controlled but delicate balance can be perturbed by alterations in the skin microbial communities, namely, dysbiosis, often due to commensals defeated by pathogens competing for space and nutrients, which leads to the occurrence of multiple cutaneous disorders. In view of this, the analysis of skin microbiota constituents in skin diseases is crucial for defining the role of commensal microbes and treatment of skin diseases. Emerging evidence shows that the ecology-based therapy of microbial transplantation has been proven as a valid therapeutic strategy for cutaneous disorders caused by skin microbial dysbiosis. Although its mechanism is not well-understood, there are already some applications for ecology-based therapy with the aim of correcting the imbalances on the cutaneous ecosystem. In this review, we summarize the interactions between dysbiosis and the cutaneous disorders, including homeostasis and dysbiosis of skin microbiota, microbial composition in skin diseases, and the mechanisms and applications of reversing or ameliorating the dysbiosis by the targeted manipulation of the skin microbiota, which may contribute to aid development of therapeutic modality for ecology-based therapy.